Global research trends in MERS-CoV: A comprehensive bibliometric analysis from 2012 to 2021 - Ahmad, Tauseef (Frontiers in Public Health, 2022)
The Middle East respiratory syndrome coronavirus (MERS-CoV) was first reported in Saudi Arabia in 2012. So far, the cases of MERS-CoV have been reported in 27 countries. The virus causes severe health complications resulting high mortality. The current study aimed to evaluate the global research trends and key bibliometric indices in MERS-CoV research from 2012 to 2021. A retrospective bibliometric and visualized study was conducted. The Science Citation Index Expanded Edition of Web of Science Core Collection database was utilized to retrieve published scientific literature on MERS-CoV. The retrieved publications were assessed for a number of bibliometric attributes. The data was imported into HistCiteTM and VOSviewer software to calculate the citations count and perform the visualization mapping, respectively. In addition, countries or regions collaboration, keywords analysis and trend topics in MERS-CoV were assessed using the Bibliometrix: An R-tool. A total of 1587 publications, published in 499 journals, authored by 6506 authors from 88 countries or regions were included in the final analysis. Majority of these publications were published as research article (n=1143). Globally, these publications received 70143 citations. The most frequent year of publication was 2016 (n=253), while the most cited year was 2014 (11517 citations). The most prolific author was Memish ZA (n=94), while the most published journal was Emerging Infectious Diseases (n=80). The United States of America (USA) (n=520) and Saudi Arabia (n=432) were the most influential and largest contributors to the MERS-CoV publications. The extensively studied research area was infectious diseases. The most frequently used author keywords other than search keywords were Saudi Arabia, SARS-CoV-2, COVID-19, epidemiology, transmission, spike protein, vaccine, outbreak, camel, and pneumonia. This study provides an insight into MERS-CoV-related research for scientific community (researchers, academicians) to understand and expand the basic knowledge structure, potential collaborations, and research trend topics. This study can also be useful for policy makers. After the emergence of MERS-CoV, a significant increase in scientific production was observed in the next four years (2013–2016). In 2021, the trend topics in MERS-CoV-related research were COVID-19, clinical characteristics and cytokine storm. Saudi Arabia had the strongest collaboration with the USA.